2022
DOI: 10.1002/clc.23936
|View full text |Cite
|
Sign up to set email alerts
|

Optimal protamine‐to‐heparin dosing ratio for the prevention of bleeding complications in patients undergoing TAVR—A multicenter experience

Abstract: Background Despite major advances, transcatheter aortic valve replacement (TAVR) is still associated with procedure‐specific complications. Although previous studies reported lower bleeding rates in patients receiving protamine for heparin reversal, the optimal protamine‐to‐heparin dosing ratio is unknown. Hypothesis The aim of this study was a comparison of two different heparin antagonization regimens for the prevention of bleeding complications after TAVR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Some authors have reported protamine dosing based on activated clotting time (ACT); for example, 10 mg protamine for ACT 201-250 s, 20 mg protamine for ACT 251-300 s, and 30 mg protamine for ACT > 300 s. 18 Protamine can also be used to partially reverse the effect of low molecular weight heparin, with dosing 1 mg of protamine per 1 mg of enoxaparin administered within 8 h, and 0.5 of mg protamine per 1 mg of enoxaparin administered within 8-12 h. 16,19 A recent observational study examined protamine dosing after TAVR, comparing partial heparin reversal (protamine-to-heparin ratio 0.4-0.6 mg for every 100 units heparin administered) versus full heparin reversal (protamine-to-heparin ratio 0.9-1.0). 20 Full heparin reversal was associated with significantly lower mortality and major bleeding (5.6% vs. 10.4%, p < 0.01), although these non-randomized results may be affected by different type of vascular closure device use between groups. 20 While these findings suggest that full heparin reversal dosing is safe and effective in the setting of TAVR, the timing of protamine with respect to heparin was not reported and may have impacted the findings.…”
Section: Pharmacology Of Protaminementioning
confidence: 90%
See 3 more Smart Citations
“…Some authors have reported protamine dosing based on activated clotting time (ACT); for example, 10 mg protamine for ACT 201-250 s, 20 mg protamine for ACT 251-300 s, and 30 mg protamine for ACT > 300 s. 18 Protamine can also be used to partially reverse the effect of low molecular weight heparin, with dosing 1 mg of protamine per 1 mg of enoxaparin administered within 8 h, and 0.5 of mg protamine per 1 mg of enoxaparin administered within 8-12 h. 16,19 A recent observational study examined protamine dosing after TAVR, comparing partial heparin reversal (protamine-to-heparin ratio 0.4-0.6 mg for every 100 units heparin administered) versus full heparin reversal (protamine-to-heparin ratio 0.9-1.0). 20 Full heparin reversal was associated with significantly lower mortality and major bleeding (5.6% vs. 10.4%, p < 0.01), although these non-randomized results may be affected by different type of vascular closure device use between groups. 20 While these findings suggest that full heparin reversal dosing is safe and effective in the setting of TAVR, the timing of protamine with respect to heparin was not reported and may have impacted the findings.…”
Section: Pharmacology Of Protaminementioning
confidence: 90%
“…Protamine can also be used to partially reverse the effect of low molecular weight heparin, with dosing 1 mg of protamine per 1 mg of enoxaparin administered within 8 h, and 0.5 of mg protamine per 1 mg of enoxaparin administered within 8–12 h 16,19 . A recent observational study examined protamine dosing after TAVR, comparing partial heparin reversal (protamine‐to‐heparin ratio 0.4–0.6 mg for every 100 units heparin administered) versus full heparin reversal (protamine‐to‐heparin ratio 0.9–1.0) 20 . Full heparin reversal was associated with significantly lower mortality and major bleeding (5.6% vs. 10.4%, p < 0.01), although these non‐randomized results may be affected by different type of vascular closure device use between groups 20 .…”
Section: Pharmacology Of Protaminementioning
confidence: 99%
See 2 more Smart Citations
“…Transcatheter aortic valve replacement (TAVR) has evolved as an alternative to surgery for the treatment of symptomatic severe aortic stenosis [1] . Since its introduction in 2002, major technical and clinical advances have been achieved, leading to continuous improvement of procedural outcomes [2] , [3] , [4] , [5] , [6] . Nevertheless, TAVR remain to be associated with several procedure-specific complications.…”
Section: Introductionmentioning
confidence: 99%